Condiciones generadas por las inundaciones urbanas en la calidad de vida de los habitantes de zonas vulnerables en la ciudad de Iquitos. Loreto. 2025 - Chuquipiondo Lopez, Xiomara (2025)
This quantitative, non-experimental, cross-sectional, correlational study aimed to analyze the conditions generated by urban flooding and their impact on the quality of life of residents of vulnerable areas. The population consisted of residents of blocks 1 and 2 of Argentina Street, in the Belén district of Iquitos, totaling 74 households, from which a sample of 50 was selected. In each household, a member over 18 years of age was interviewed using a structured survey, whose reliability was validated with a Cronbach's alpha of 0.848 for 14 items evaluated. In the inferential analysis, the Shapiro-Wilk test was applied to verify data normality. When variables with a non normal distribution were identified, the Spearman correlation test was used. The results show that vulnerability to flooding is significantly related to deficiencies in the sewerage system, a lack of urban planning, and economic constraints. Recurrent flooding has increased the incidence of infectious diseases and the proliferation of vectors, affecting the population's physical and emotional health. Furthermore, the perception of well-being and safety has deteriorated, deepening the state of vulnerability. The adaptation strategies observed are mostly reactive, individual, and limited in scope. Mitigation actions promoted by local authorities are perceived as insufficient for comprehensive risk management. It is concluded that deficiencies in the sewerage system primarily affect public health and the environment, generating indirect economic consequences for families. In this context, the need to implement comprehensive, sustainable interventions aimed at strengthening community resilience to extreme hydrometeorological events is reaffirmed.